Z‐Scheme 2D/2D Heterojunction of Black Phosphorus/Monolayer Bi 2 WO 6 Nanosheets with Enhanced Photocatalytic Activities - Hu, Jundie; Chen, Dongyun; Mo, Zhao; Li, Najun; Xu, Qingfeng; Li, Hua; He, Jinghui; Xu, Hui; Lu, Jianmei (Angewandte Chemie International Edition, 2019)
Black phosphorus (BP), a star‐shaped two‐dimensional material, has attracted considerable attention owing to its unique chemical and physical properties. BP shows great potential in photocatalysis area because of its excellent optical properties; however, its applications in this field have been limited to date. Now, a Z‐scheme heterojunction of 2D/2D BP/monolayer Bi 2 WO 6 (MBWO) is fabricated by a simple and effective method. The BP/MBWO heterojunction exhibits enhanced photocatalytic performance in photocatalytic water splitting to produce H 2 and NO removal to purify air; the highest H 2 evolution rate of BP/MBWO is 21042 μmol g −1 , is 9.15 times that of pristine MBWO and the NO removal ratio was as high as 67 %. A Z‐scheme photocatalytic mechanism is proposed based on monitoring of . O 2 − , . OH, NO 2 , and NO 3 − species in the reaction. This work broadens applications of BP and highlights its promise in the treatment of environmental pollution and renewable energy issues.